Disaster Management Based on The Perspective of Inter-Religious Connection and Local Wisdom ANTAR AGAMA DAN PENGHARGAAN TERHADAP KEBUDAYAAN LOKAL - M. Alie Humaedi (Balai Penelitian dan Pengembangan Agama Semarang, 2015)
In each disaster response done by volunteers, sometimes there are emerging issuesof religious dissemination and the volunteers are expulsed because of breaching thelocal values. The use of mosque and local leaders are also supposed to have such issues. Inmanycases, the framework of interfaith and local culture sperspectiveis often forgotten. The issue is how to implement of humanitarian activity based on theinterfaith and local cultures perspective? This is a qualitative research using in-depthinterviews, observation, focus group discussions, and documentation insix locations.Those locations that found the basis of humanitarian activity, particularly in the roleof mosques and the development of the effectiveness of local leaders, as well as havereliedon interfaith and the local culture perspective. This theoretical constructioncan be apart of the strategic formulation and code of conduct for humanitarianorganizations when dealing with communities from different religions and cultures..